Fabrication and properties of NiCr/CNTs nanocomposite coatings prepared by High Velocity Oxy-Fuel Spraying - D. Deesom (2018)
© 2016 Elsevier B.V. Nickel-Chromium (NiCr)/CNTs composite coatings were deposited onto mild steel substrates by High Velocity Oxy–Fuel Spraying (HVOF). The composite powder feedstock was prepared by: (1) mixing by ball milling NiCr powder with 0, 0.5, 1 wt% CNTs for 48 h: (2) growing carbon nanotubes on NiCr powder using chemical vapor deposition (CVD) technique at 650 °C for 60 min under ethanol atmosphere. The microstructure of NiCr-CNTs powder was characterized by scanning electron microscope (SEM) and transmission electron microscope (TEM). Chemical compositions of the different powders were studied using X-ray Diffractometry (XRD) and Energy Dispersive X-ray spectroscopy (EDX) techniques. Porosity and Vickers hardness of the coatings were also measured. Sliding wear tests were carried out using a pin-on-disk apparatus. Dense coatings which contained mainly Nickel phase could be achieved. Thickness of the coatings was about 300–350 μm with a similar % porosity of 0.49–1.01 vol%. Vickers hardness tests show that the hardness of Nickel-Chromium/CVDCNTs was 20% higher than that of a pure Nickel-Chromium coating leading to a better wear resistance. Polarization test showed that carbon nanotubes could improve the corrosion resistance of the coating. The main objectives of this study are to prepare the NiCr/CNTs composite feedstock powders and also to evaluate the properties of HVOF coatings from those powders.